Under the loupe of solid-state chemistry: a brief introduction to the carbodiimide/cyanamide family - Bourakhouadar, Hicham (2023)
Metal cyanamides and carbodiimides are an exciting group of compounds in solid state chemistry. They have been widely studied in recent years, and a large number of compounds have been reported that now incorporate alkali, alkaline earth, main group, transition, and rare earth metals. This work is an introduction to this family, in which we describe the forms of crystallization, methods of synthesis and some of their reported and potential applications in Li-Ion & Na-Ion batteries, as light-emitting diodes and photoluminescent materials.